Migration Experiences of A Young Arab Muslim Woman in the West from A Contemporary Young Adult English Novel - Maria Ulfa; Diva Rizkia Nuralisa; Tinezia Putri Khairana; Annisa Nur Chaliza; Azahra Dea Adrian; Adinda Angel Aulia D. P. (Universitas Negeri Makassar, 2022)
Abstract. This article discusses migration experiences of a young migrant Arab Muslim woman in a western country portrayed in a contemporary electronic (digital literature) English young adult novel entitled Alina Kanaan written by Rhonda Boldt published in 2021 by Wattpad, a social storytelling application. This research aims to explain migration experiences of a young migrant Arab Muslim woman from Palestine in America through the analysis of the main migrant character with her problems related to hybridity, ambivalence & adjustment, and abandonment & return. The result shows that the novel has many diaspora issues especially through the experiences of migration of the main female character, Alina Kaanan as a young migrant Arab Muslim migrant woman in America. She struggles to face problems and to integrate to the new society through her hybrid identity, ambivalence & adjustment mainly through three issues namely language adjustment, food & drink selection, and avoding “free sex culture,” as well as through the aspects of abandonment and return. Eventhough she receives bad threatments namely discrimination and racism toward Muslims in America from a number of Americans, she decides not to return to her homeland but to continue to live in the hostland America and pursuing her dream to be a successful singer as the winner of American Idol by maintaining her identiy as a migrant Arab Muslim woman and an American resident at the same time. Keywords: Diaspora, Migration, Arab Muslim Woman, Electronic literature, Wattpad, Young Adult English Novel